Optimising upload bandwidth for quality of VCR operations in P2P VoD systems. (7th May 2010) - Chung, Tzu-Meng; Huang, Shih-Chieh; King, Chung-Ta; Chang, Chiu-Ping
Many P2P VoD systems have been proposed, but only few can support VCR operations. Most of the works require very well provisioned source servers to guarantee the quality. The challenge is to do the same without requiring well provisioned source servers. In this paper, we take the heterogeneity of bandwidth into consideration, and also consider the practical case in which the capacity of the streaming buffer is limited. With these conditions, we formulate the problem as an upload bandwidth optimisation problem. We first prove that this problem is NP-hard and then propose an optimal dynamic programming solution.